The Relationship between Authentic Materials and Cooperative Learning Strategy towards EFL Students’ Reading Comprehension - Nurlela, Siti; Suryoputro, Gunawan (Journal of ELT Research, 2016)
EFL (English as a Foreign Language) students of vocational high schools are requested to have skillful reading strategies to comprehend specific texts in English. To have a good comprehension, they utilize not only their strategies but also interesting and suitable texts. Therefore, this current study investigated the correlation between students’ perception of the authentic materials and cooperative learning strategy towards students’ reading comprehension. The data of the reading comprehension tests and the students’ perception were analyzed using the multiple regression. The result revealed that (1) there was positive correlation between students’ perception of the authentic materials and students reading comprehension, (2) there was significant positive effect of cooperative learning strategy towards reading comprehension, and (3) there was significant positive effect of reading materials towards cooperative learning strategy. These findings suggested that the choice of authentic materials could motivate students to comprehend ESP texts. Besides this, by doing cooperative learning strategy, the scaffolding could happen so that they could share their comprehension. In spite of its limitation, this study could have certain pedagogical implications to reading classroom activities.